Joint Specificity and Lateralization of Upper Limb Proprioceptive Perception. Issue 3 (June 2022) - Chebel, Najib M. Abi; Roussillon, Nadege A.; Bourdin, Christophe; Chavet, Pascale; Sarlegna, Fabrice R.
Proprioception is the sense of position and movement of body segments. The widespread distribution of proprioceptors in human anatomy raises questions about proprioceptive uniformity across different body parts. For the upper limbs, previous research, using mostly active and/or contralateral matching tasks, has suggested better proprioception of the non-preferred arm, and at the elbow rather than the wrist. Here we assessed proprioceptive perception through an ipsilateral passive matching task by comparing the elbow and wrist joints of the preferred and non-preferred arms. We hypothesized that upper limb proprioception would be better at the elbow of the non-preferred arm. We found signed errors to be less variable at the non-preferred elbow than at the preferred elbow and both wrists. Signed errors at the elbow were also more stable than at the wrist. Across individuals, signed errors at the preferred and non-preferred elbows were correlated. Also, variable signed errors at the preferred wrist, non-preferred wrist, and preferred elbow were correlated. These correlations suggest that an individual with relatively consistent matching errors at one joint may have relatively consistent matching errors at another joint. Our findings also support the view that proprioceptive perception varies across upper limb joints, meaning that a single joint assessment is insufficient to provide a general assessment of an individual's proprioception.